Anti-Sticking sand coatings for foundry moulds and cores - V. V. Ectov; V. N. Ectova (Литьë и металлургия, 2000)
Are presented the elaborated compositions of self-hardening anti-sticking sand coatings with high thermal resistance for foundry moulds and cores for production of cast iron castings.